A vigilant observation to pregnancy associated listeriosis in Africa: Systematic review and meta-analysis. - Alene Geteneh; Sirak Biset; Selamyhun Tadesse; Alemale Admas; Abdu Seid; Demeke Mesfin Belay (Public Library of Science (PLoS), 2022)
The burden of human listeriosis, an emerging food-borne illness would be higher in Africa due to poor food processing practices. The severity of the disease and the high case fatality rate make human listeriosis an important public health problem. Besides, pregnant women and their fetuses are at higher risk of gaining human listeriosis. Thus, we planned to estimate the pooled prevalence of pregnancy-associated human listeriosis in Africa. Primary studies were exhaustively searched using PubMed, Cochrane, Web of Science, Google Scholar, and University of Gondar online research repository. Observational studies (cross-sectional) revealing the pregnancy-associated human listeriosis were incorporated. Eligible studies were selected and critically appraised for quality using the Joanna Briggs Institute (JBI) quality appraisal checklist. The required data were extracted and exported to Stata version 14 for meta-analysis. The pooled prevalence of pregnancy-associated human listeriosis in Africa was estimated using a weighted inverse random effect model. Sensitivity and sub-group analysis were conducted for evidence of heterogeneity. Among 639 reviewed articles, 5 articles were eligible with total study participants of 621. The pooled prevalence of pregnancy-associated listeriosis was found to be 5.17% (95% CI, 1.51, 8.82). The pooled level resistance of isolates was high. Cotrimoxazole and erythromycin were the relative choices of antibiotics for pregnancy-associated listeriosis in Africa. The burden of pregnancy-associated listeriosis in Africa was higher with an increased level of antibiotic resistance. Therefore, we recommend due attention to the deadly emerging disease in terms of health educations and the role of food hygiene particularly for risk groups, pregnant women. The antibiotics of choice should be after performing drug susceptibility test.